2019
DOI: 10.1038/s41467-019-10100-8
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome biogenesis during cell cycle arrest fuels EMT in development and disease

Abstract: Ribosome biogenesis is a canonical hallmark of cell growth and proliferation. Here we show that execution of Epithelial-to-Mesenchymal Transition (EMT), a migratory cellular program associated with development and tumor metastasis, is fueled by upregulation of ribosome biogenesis during G1/S arrest. This unexpected EMT feature is independent of species and initiating signal, and is accompanied by release of the repressive nucleolar chromatin remodeling complex (NoRC) from rDNA, together with recruitment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
173
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(192 citation statements)
references
References 79 publications
17
173
2
Order By: Relevance
“…Moreover, we showed that the migratory capability of the PANC-1 cells was inhibited, but this could not be correlated with the expression of EMT markers. The lack of vimentin modulation is in line with the results of Prakash and collaborators in NNuMG cells treated with CX-5461 [14]. However, we found an upregulation of SNAIL1 mRNA expression after CX-5461 exposure in PDAC-3 and SUIT-2-28 cells, whereas the previous study [14] shows only an increase of SNAIL1 in transforming growth factor β (TGF-β) stimulated cells treated with CX-5461.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, we showed that the migratory capability of the PANC-1 cells was inhibited, but this could not be correlated with the expression of EMT markers. The lack of vimentin modulation is in line with the results of Prakash and collaborators in NNuMG cells treated with CX-5461 [14]. However, we found an upregulation of SNAIL1 mRNA expression after CX-5461 exposure in PDAC-3 and SUIT-2-28 cells, whereas the previous study [14] shows only an increase of SNAIL1 in transforming growth factor β (TGF-β) stimulated cells treated with CX-5461.…”
Section: Discussionsupporting
confidence: 91%
“…The high sensitivity of the tested PC cells to CX-5461 and previous findings suggesting that ribosome biogenesis contributes to metastatic cancer progression [14] prompted us to investigate the effect of this drug on cell migration, using the wound healing assay.…”
Section: Cx-5461 Inhibits Pancreatic Cancer Cell Growth In Nanomolar mentioning
confidence: 99%
“…A salient feature of spindle MBCs, which are highly proliferative and exhibit pathological evidence of EMT with elongated cancer cells, is upregulated expression of E2F and MYC pathway proteins, ribosomal proteins and transcriptional and translational processes. These findings are intriguing based on data showing that E2F and MYC are key drivers of cancer cell proliferation and EMT processes, where ribosome biogenesis and increased translation play an essential role 30,31 . These data also suggest that spindle MBC have a deregulated balance between translation and metabolic pathways, which needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR positively regulates several processes involved in ribosome biogenesis, including rRNA transcription as well as the synthesis of ribosomal proteins and components of ribosome assembly [67]. The mTORC2 component rictor is recruited to the nucleolar compartment during epithelial-to-mesenchymal transition (EMT)-associated ribosome biogenesis [68]. The role of rictor or mTORC2 in this compartment requires further investigation.…”
Section: Protein Synthesismentioning
confidence: 99%